Nonextraction Management of Severely Malaligned and Constricted Upper Arch - Manar K. Hajrasi; Ahmad A. Al-Fraidi; Abdulkarim A. Hatrom; Ali H. Hassan (Case Reports in Dentistry)
This case report presents the treatment of a 12-year-old female with a severely crowded upper arch, severely palatally displaced upper premolars and lateral incisors, large midline diastema, lower midline deviation to the right, class III dental and skeletal relationships due to mild maxillary deficiency, retroclined lower incisors, straight profile, and retrusive lips. A nonextraction treatment approach is described, in which the upper and lower arches were expanded to their original three dimensions using a trihelix expander, a lip bumper appliance, and a fixed orthodontic appliance. Retention was also planned in accordance with the original malocclusion, which inclued a full-time-wear upper wraparound retainer, upper and lower anterior fixed lingual retainers, upper frenectomy, and fibrotomy for rotated teeth. Conclusion. Severe malalignment of teeth does not necessarily require extraction treatment. Gaining space is an art that requires a proper assessment of the anteroposterior and transverse dimensions of alveolar arches, lip prominence, and postorthodontic stability.